MapSPAM2020_AdaptationAtlas_SSA - Wood-sichra, Ulrike; Steward, Peter Richard; Rosenstock, Todd Stuart; Youngberg, Brayden; Guo, Zhe; Zhou, Shuang (2026)
The MapSPAM 2020 SSA Adaptation Atlas Dataset is a regional adaptation and extension of IFPRI’s global MapSPAM 2020, specifically tailored for Sub-Saharan Africa (SSA) for the Africa Agriculture Adaptation Atlas project. It compiles sub-national crop production statistics for 42 major crops, harmonized with FAOSTAT country totals and supplemented by multiple national and sub-national sources. These production statistics are disaggregated into 6 production systems: irrigated, high-input rainfed, low-input rainfed, rainfed subsistence, all rainfed, and all.